2020
DOI: 10.7203/realia.25.15780
|View full text |Cite
|
Sign up to set email alerts
|

How prior knowledge, learning, teaching and assessment affect students’ achievements in Mathematics

Abstract: In this study we investigate how prior knowledge, the comprehensive learning approach, problem-based teaching and assessment influence students’ basic-learning skills in Mathematics at the university level. To do so, we employed a quasi-experimental research design and a structured questionnaire. Two experimental groups and two control groups of students were involved. We found a negligible correlation between prior knowledge and basic-learning skills but a positive correlation between prior knowledge and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
2
0
2
Order By: Relevance
“…La Tabla 6 muestra que los estudiantes más favorecidos con saberes previos no se perjudican con los niveles de mediación pedagógica, pues sus recursos cognitivos les ayudan a enfrentar los desniveles en tutoría pedagógica. Esto se debe a que, como demuestran en sus estudios Dong et al;Xhomara (2020;2020), los estudiantes con mejores saberes previos tienen una mejor compromiso en su aprendizaje; es decir, como bien afirma Hirsch Jr. (1997), el capital cultural permite tener más conocimientos. Otros estudios que tienen en cuenta las tres variables de estudio de la presente investigación (Berkhout et al, 2017;Kuang et al, 2020;Roll et al, 2018;van Riesen et al, 2018bvan Riesen et al, , 2018avan Riesen et al, 2022) dejan en evidencia que los estudiantes menos favorecidos cognoscitivamente son los que se perjudican con el escaso apoyo pedagógico.…”
Section: Discussionunclassified
“…La Tabla 6 muestra que los estudiantes más favorecidos con saberes previos no se perjudican con los niveles de mediación pedagógica, pues sus recursos cognitivos les ayudan a enfrentar los desniveles en tutoría pedagógica. Esto se debe a que, como demuestran en sus estudios Dong et al;Xhomara (2020;2020), los estudiantes con mejores saberes previos tienen una mejor compromiso en su aprendizaje; es decir, como bien afirma Hirsch Jr. (1997), el capital cultural permite tener más conocimientos. Otros estudios que tienen en cuenta las tres variables de estudio de la presente investigación (Berkhout et al, 2017;Kuang et al, 2020;Roll et al, 2018;van Riesen et al, 2018bvan Riesen et al, , 2018avan Riesen et al, 2022) dejan en evidencia que los estudiantes menos favorecidos cognoscitivamente son los que se perjudican con el escaso apoyo pedagógico.…”
Section: Discussionunclassified
“…Given this, student-faculty interaction is related to the highest levels of classroom engagement, which on the other hand makes possible students' cognitive skills development (Kim & Lundberg, 2016). Xhomara (2020) indicated that prior knowledge, problem-based teaching, the comprehensive learning approach and assessment explained 50% of the variance in the levels of course outcomes; meanwhile, according to Cox and Orehovec (2007), out-of-class student-faculty interaction can be of five types which can be included in disengagement, incidental contact, functional interaction, personal interaction, and mentoring. Furthermore, the student-faculty interaction is saliant for building a collaborative and productive climate to improve the learning process and to increase course outcomes (Cole & Griffin, 2013;Kim & Sax, 2009), can play a crucial role in fostering student motivation, and engagement in learning (Muñoz, Baik, & Lodge, 2020), and is a powerful predictor of student learning (Kuh & Hu, 2001;Terenzini, Pascarella, & Blimling, 1996).…”
Section: Student-faculty Interaction and Its Effectsmentioning
confidence: 99%
“…Other studies provided evidence that faculty-student interaction, individual study work and lecturer support have an impact on course outcomes (Delaney, 2008;Xhomara, 2020), academic achievement (Hylton, 2013;Lamport, 1993), and facultystudent relationships can also predict grades (Micari & Pazos, 2012). Likewise, the student-faculty interaction is connected to higher student grade point averages, and higher student satisfaction (Bernstein, 2021).…”
Section: Student-faculty Interaction and Its Effectsmentioning
confidence: 99%
“…Pengetahuan awal siswa yang seringkali familiar dengan istilah prior knowledge sebagai suatu kumpulan pengetahuan serta pengalaman siswa yang didapatkannya selama belajar, lalu pengetahuan tersebut digunakan oleh siswa menuju ke dalam pengalaman belajar yang baru (Ningsih & Retnowati, 2020;Xhomara, 2020). Menurut pernyataan ini, pengetahuan awal ini dapat dijadikan modal awal bagi siswa dalam memahami pengetahuan baru.…”
Section: Pendahuluanunclassified